PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR - Linda Tri Utami; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACT This study aims to determine the effect of Return On Assets, Net Profit Margin, Current Ratio, Debt To Quality Ratio and Inventory Turnover on Disclosure of Corporate Social Responsibility in Manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The samples amounted to 30 Manufacturing companies taken by Purposive Sampling techniques, namely the selection of samples based on certain criteria. The data analysis technique used is multiple linear regression. The results of the study is Return On Asset, Current Ratio, and Debt To Equity Ratio variables, do not significantly influence Corporate Social Responsibility, while Net Profit Margin, and inventory turnover has a positive effect on Corporate Social Responsibility. Simultaneously ROA, NPM, RC, Debt To Quality Ratio and Inventory Turnover have an effect on Corporate Social Responsibility. Keywords : Return On Asset, Net Profit Margin, Debt To Quality Ratio, Current Ratio, Inventory Turnover, Corporate Social Responsibility.